MADONNA’S FOUR-DECADE INFLUENCE: BRAND STRATEGY AND GLOBAL IMPACT OF THE CELEBRATION TOUR RIO DE JANEIRO - Pedro BELTRÁN CUERVO; Cecilia VALLEJOS PARÁS (Styles of Communication)
Madonna, a well-known musician and entertainer who has remained at the top of her game for over 40 years, is also a marketing and brand strategist. This research explores the evolution of global perceptions around her brand following her 2024 Celebration Tour, culminating in a record-breaking closing concert in Rio de Janeiro attended by 1.6 million people. Grounded in the theoretical frameworks of Aaker’s and Keller’s brand equity models, the study employs a quantitative methodology using a self-administered online questionnaire distributed among Madonna’s international fan communities. The survey examined the most important components of brand equity. The results suggest that Madonna has a firm stronghold in the entertainment world. Notably, most respondents reported that the 2024 tour enhanced her brand’s value on a global scale. This longstanding impact shows her capacity to continue to be an iconic cultural figure and confirms the longevity and power of her brand.